2004
DOI: 10.1271/bbb.68.565
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Cloning and Characterization of a Secreted Luciferase from the Luminous Japanese Ostracod,Cypridina noctiluca

Abstract: A secreted luciferase from the marine ostracod, Vargula hilgendorfii, is a useful tool for gene expression assays in living mammalian cells. We have cloned the cDNA of a new secreted luciferase from the ostracod Cypridina noctiluca, which inhabits the coast of Japan. C. noctiluca luciferase consists of 553 amino acid residues with a molecular mass of 61,415 Da, as deduced from the nucleotide sequence. The homologies of nucleotide and amino acid sequences with V. hilgendorfii luciferase are 79.2% and 83.1%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
101
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 11 publications
1
101
0
2
Order By: Relevance
“…5b), values better than those referred to other luciferase, such as Gaussia luciferase, Cypridina noctiluca luciferase and Vargula hilgendorfii luciferase [25][26][27] which evidence negligible activity after 60 min incubation at 65°C.…”
Section: Temperature and Ph Effect On Enzyme Activity And Stabilitymentioning
confidence: 74%
“…5b), values better than those referred to other luciferase, such as Gaussia luciferase, Cypridina noctiluca luciferase and Vargula hilgendorfii luciferase [25][26][27] which evidence negligible activity after 60 min incubation at 65°C.…”
Section: Temperature and Ph Effect On Enzyme Activity And Stabilitymentioning
confidence: 74%
“…To construct the SeV vector, marker genes were inserted into a unique NotI site created in SeV genomic cDNA as described (13). cDNAs encoding enhanced green fluorescent protein (EGFP), Cypridina noctiluca luciferase (CLuc), and fibroblast growth factor 1-proteoglycan fusion protein (PG-FGF-1) were amplified by PCR to add the transcription initiation signal (S) and termination signal (T), using pEGFP-1 (Clontech, Mountain View, CA), pCLm (14), and pMex-RyuII (15) as templates, respectively. The detailed procedure for the construction of the vector cDNA with marker genes is described in supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To elucidate how oscillatory secretion is generated during chondrogenesis, it was examined which factors determine secretion activity in prechondrogenic cells. The secretory activity was monitored using a reporter carrying the secreted Cypridina luciferase (CLuc) gene fused to ACTIN promoter (Nakajima et al 2004). It was shown that an inhibitor of mitochondrial oxidative phosphorylation oligomycin suppressed CLuc secretion in prechondrogenic cells (Fig.…”
Section: Cmentioning
confidence: 99%